Analisis Sistem Pengendalian Internal Pada Proses Penggajian Dan Pengupahan Dengan Studi Kasus Pada PT. Semesta Gemilang Karyatama (Sgk Plywood) - Ahmad Sya’roni; Syamsul Bahri; Dwi Anggarani; Irfan Fatoni (Trending: Jurnal Manajemen dan Ekonomi, 2023)
The internal control system for payroll and wages is a system to control and minimize the occurrence of problems in the payroll and wage process. The occurrence of dual duties, authorities and responsibilities in PT. Semesta Gemilang Karyatama (SGK Plywood) is a problem that can arise within the company. The purpose of this study was to analyze the internal control system in the payroll and wage processes of PT. Universe Gemilang Karyatama (SGK Plywood). this is done to find out the payroll and wage control system that is applied then to analyze the factors that lead to potential problems at PT. Semesta Gemilang Karyatama (SGK Plywood) and provide suggestions for improvements to the existing system. This research was conducted using descriptive and qualitative methods by collecting data through direct observation of objects, interviews with relevant sources, analyzing existing documents. From the research results, PT. Semesta Gemilang Karyatama (SGK Plywood) is still not implementing good practices in accordance with existing elements with dual responsibilities and authorization fully charged to the leadership so that existing controls are still not optimal. By separating the responsibilities properly and the responsibility is given to the competent part in their field to authorize it can minimize errors that can occur at PT. Universe Gemilang Karyatama (SGK Plywood).